ATP1A3 variants and slowly progressive cerebellar ataxia without paroxysmal or episodic symptoms in children. (7th September 2020) - Sasaki, Masayuki; Sumitomo, Noriko; Shimizu‐Motohashi, Yuko; Takeshita, Eri; Kurosawa, Kenji; Kosaki, Kenjiro; Iwama, Kazuhiro; Mizuguchi, Takeshi; Matsumoto, Naomichi
Abstract : A heterogeneous spectrum of clinical manifestations caused by mutations in ATP1A3 have been previously described. Here we report two cases of infantile‐onset cerebellar ataxia, due to two different ATP1A3 variants. Both patients showed slowly progressive cerebellar ataxia without paroxysmal or episodic symptoms. Brain magnetic resonance imaging revealed mild cerebellar cortical atrophy in both patients. Whole exome sequencing revealed a de novo heterozygous variant in ATP1A3 in both patients. One patient had the c.460A>G (p.Met154Val) variant, while the other carried the c.1050C>A (p.Asn350Lys) variant. This phenotype was characterized by a slowly progressive cerebellar ataxia since the infantile period, which has not been previously described in association with ATP1A3 variants or in ATP1A3 ‐related clinical conditions. Our report contributes to extend the phenotypic spectrum of ATP1A3 mutations, showing paediatric slowly progressive cerebellar ataxia with mild cerebellar atrophy alone as an additional clinical presentation of ATP1A3 ‐related neurological disorders. Abstract : This article is commented on by Ng on pages 12‐13 of this issue.